A crosslinked polymer skin barrier film for moderate to severe atopic dermatitis: A pilot study in adults - Bouthillette, Melaney; Beccati, Daniela; Akthakul, Ariya; Ramadurai, Nithin; Nashat, Amir; Langer, Robert; Anderson, R. Rox; Sakamoto, Fernanda H. (Journal of the American Academy of Dermatology, 2020)
Occlusive treatments are a mainstay in atopic dermatitis (AD) management but may not be well tolerated or lack compliance. A comfortable, semiocclusive, artificial skin barrier that is well tolerated, provides protection, and reduces water loss is needed. To evaluate the potential tolerability and therapeutic benefits of a crosslinked polymer layer (XPL) in adults with AD. A single-center, open-label pilot study was conducted involving 10 subjects with moderate to severe AD. Subjects applied XPL up to twice daily for 30 days on a selected treatment area. Investigator's Global Assessment, clinical signs of eczema, and pruritus were assessed on days 1, 3, 5, 15, and 30. Film durability and patient satisfaction were also evaluated. Investigator's Global Assessment scores improved from moderate to severe at baseline to clear to almost clear in 8 of 9 patients at day 30. Pruritus improved from trace to severe itching (baseline) to all subjects having trace to no itching at day 30. There was 1 adverse event of mild exudative dermatitis. The study was limited by small sample size, open-label design, and lack of control. XPL may be an effective adjuvant in AD treatment. A larger study with a control group is warranted.